Effect of assembly pressure on the performance of a bendable polymer electrolyte fuel cell based on a silver nanowire current collector. (1st September 2017) - Park, Taehyun; Chang, Ikwhang; Jung, Ju Hae; Lee, Ha Beom; Ko, Seung Hwan; O'Hayre, Ryan; Yoo, Sung Jong; Cha, Suk Won
Abstract: This work investigates the effect of assembly pressure on the performance of a bendable polymer electrolyte fuel cell based on silver nanowire current collectors. We define assembly pressure as the compressive stress exerted by the bendable fuel cell flow structure on the membrane electrode assembly. The performance of the bendable fuel cell increases with increasing assembly pressure while the corresponding ohmic and charge transfer resistances of the fuel cell decrease. While in certain circumstances bending can increase fuel cell performance because it increases the assembly pressure internally exerted on the MEA, we also find that deformation of the flow structures upon bending the fuel cell can negatively affect performance due to non-uniform disruptions in the distribution of reactants. We extract the key electrochemical parameters that are most sensitive to assembly pressure and develop a simulation model for bendable fuel cells using these parameters. This model is validated against the experimental data of here and previous studies, thereby showing the feasibility of engineering the bendable fuel cells for various demands. Highlights: Bendable polymer electrolyte fuel cell was fabricated using silver nanowires. Effect of assembly pressure on bendable fuel cell was investigated experimentally. Causes of performance loss by bending in bendable fuel cell were figured out. Simulation model of bendable fuel cell was established based on experimental data. Simulation model predicts performances of other bendable fuel cells in literatures.